Pendidikan Islam Berbasis Pesantren - Abdul Muid; Nailatus Saadah Maziyah (cendekia citra gemilang, 2026)
This study Islamic education based on boarding school systems has played a strategic role in shaping students’ character, morality, and spirituality. Islamic boarding schools not only teach Islamic knowledge but also foster personal development by instilling moral values and character traits that reflect the core principles of Islam. In the contemporary era, Islamic boarding schools have maintained their Islamic identity while simultaneously developing practical skills and formal curricula to address global challenges. These institutions are highly regarded for their comprehensive educational approach, which encompasses not only academic achievement but also emotional development and physical training. Life in Islamic boarding schools cultivates discipline, independence, and responsibility, while traditional learning methods such as sorogan, bandongan, and halaqah provide students with a profound understanding of Islamic teachings. Furthermore, the significant role of the kiai (Islamic scholar or teacher) as a role model contributes greatly to character formation and strengthens the relationship between teachers and students. However, the evolution of Islamic education in boarding schools has also introduced new challenges, including the demands of globalization, digitalization, and modernization. Therefore, Islamic boarding schools need to modernize their educational systems by improving teacher quality, adopting new technologies, and enhancing administrative management. Through these efforts, Islamic boarding schools are expected to continue fulfilling their educational mission and producing students who possess broad perspectives and a deep understanding of both Islam and the wider world.